Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1016/s0020-7292(99)00037-5
|View full text |Cite
|
Sign up to set email alerts
|

Cervical ectopy and the transformation zone measured by computerized planimetry in adolescents

Abstract: Computerized planimetry provides standardized measurements. Douching and sexual activity may decrease ectopy through increased squamous metaplasia. Hormonal contraceptives were not associated with ectopy in adolescents. However, long-term progestin use may decrease T zone size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 13 publications
2
20
1
2
Order By: Relevance
“…Duration of oral contraceptive use had no apparent influence on the prevalence of C trachomatis infection-as reported also by Munk et al 12 and Jacobson et al 30 The lack of association between parity and C trachomatis infection observed by us is in line with the study by Munk et al 12 but it contrasts with the study by Bagshaw et al…”
Section: Discussionsupporting
confidence: 88%
“…Duration of oral contraceptive use had no apparent influence on the prevalence of C trachomatis infection-as reported also by Munk et al 12 and Jacobson et al 30 The lack of association between parity and C trachomatis infection observed by us is in line with the study by Munk et al 12 but it contrasts with the study by Bagshaw et al…”
Section: Discussionsupporting
confidence: 88%
“…This finding is biologically plausible, given that the life cycle of HPV is dependent on host cell replication and differentiation, which are characteristic of squamous metaplasia occurring in the cervical transformation zone; basal cells, the target cells for HPV infection, are most accessible in the transformation zone which, in young women, increases in size with time from menarche, independent of sexual and other reproductive factors. 7,8 Our findings contradict studies that suggest that a short interval between menarche and first intercourse increases the risk of HPV infection. 1,2 In these studies, women were first sampled some years after first intercourse; as the authors concede, there is no evidence that infection was acquired during the hypothesized period of increased vulnerability.…”
Section: Discussioncontrasting
confidence: 84%
“…Some authors have assessed the visual demarcation between endocervical columnar cells and the rest of the cervix, with this area defined as ectopy. Others have used computerized images, as in the current study, although in some studies no correlation between hormonal contraception and ectopy was found [4].…”
mentioning
confidence: 66%
“…A number of factors have been suggested as potentially affecting cervical maturation, including trauma, hormonal status, douching, age of coitarche, and number of sexual partners [4,5]. Other factors-such as noncoital sexual activities, the use of condoms, vaginal spermicides, or progestinonly contraceptives, could potentially play a role; however such factors have either not been a focus of investigation, or the published studies have not been sufficiently large to answer the questions.…”
mentioning
confidence: 99%